Gestão e fiscalização de contratos de serviços terceirizados em uma Instituição Federal de Ensino - Zucoloto, Izabel Eliani (2019)
The outsourcing of services of the middle activities by the Public Administration inserts a crucial aspect regarding the monitoring and supervision of administrative contracts, which involve public resources and are directed to the common good. Not infrequently, the citizen is faced with unfinished services that cost millions, reflecting on schedule delays, budget additives, etc. Consequently, there is the waste of public resources. This research analyzes the fundamental aspects of the supervision activity in the Federal Institute of Espírito Santo, detecting in the literature the relevant aspects for professional performance in the management and supervision of outsourced services contracts and diagnosing in the Federal Institute of Espírito Santo how those management and supervision of outsourced service contracts happen. A descriptive research was carried out, the application of a questionnaire with open and closed questions and a documentary research were adopted as the methodological tools. In the theoretical reference part, initially, the administrative reforms are reported with the purpose of making the Public Administration more operative, efficient and effective. Afterwards, there is a discussion about outsourcing, biddings, administrative contracts, as well as its execution and supervision, and also a synthesis of researches done on the subject. Finally, it is concluded that there are weaknesses in the management and supervision processes in the studied institution. This indicates the need to introduce a real management and supervision policy, making improvements, in particular, in the training and betterment of the public servers designated to inspect outsourced services contracts and creating mechanisms to subsidize them in this important task. Based on the result, a simple and objective action plan was drawn up, pointing out suggestions to make the management and the supervision more operative, efficient and effective.